PHARMACOGNOSTIC STANDARDIZATION, PHYSICO AND PHYTOCHEMICAL EVALUATION OF AERIAL PARTS OF MENTHA ARVENSIS LINN. (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
The present study deals with the macroscopical and microscopical studies of aerial parts of Mentha arvensis Linn. Microscopically, aerial parts showed glandular trichomes, helical to spiral xylem, palisade tissues with columnar cells, diacytic stomata. Powder microscopical examination showed the presence of glandular and uni to multi celled trichomes, helical to spiral xylem vessel, stomatal epidermal cells, abundant xylem vessels with pitted thickenings, abundant thin walled parenchymatius cells, epidermis with cuticle and collenchymatous cells, parenchymatous cells with reddish tannin contents. Physicochemical parameters and preliminary phytochemical studies of the powdered aerial parts were also carried out. Total ash was approximately sixteen and four times more than acid insoluble and water soluble ash, respectively. Water soluble extractive was slightly higher than ethanol soluble extractive. T.L.C. of petroleum-ether, chloroform and ethanol extract showed eight spots, nine spots and six spots, respectively. Phytochemically, it exhibited alkaloids, glycosides, steroids and sugars. These findings might be useful to supplement information in regard to its identification parameters assumed significantly in the way of acceptability of herbal drugs in present scenario lacking regulatory laws to control quality of herbal drugs.